BIOPRODUCT DEVELOPMENT TECHNOLOGY FROM MICROBE TO BUILD ENTREPRENEURSHIP OF PENJARINGAN SARI RUNGKUT RUSUNAWA RESIDENT - Purkan Purkan; Sofijan Hadi; Fatiha Khairunnisa; Afaf Baktir; Sri Sumarsih (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
Introduction: in general, residents of flats are a low-income group of people. Economic improvement for Rusunawa residents with concrete efforts is needed to be able to alleviate poverty. Purpose: the community service program's touch is aimed at initiating entrepreneurship among the residents of the flats through providing training on making a variety of microbial bioproducts with economic value, targeting PKK Rusunawa Penjaringan Sari, Rungkut-Surabaya mothers. Method: Community service activities are carried out in 3 stages, namely (1) survey and coordination, (2) workshops and training on making bioproducts from microbes, and (3) Evaluation of activities. Results: Community service participants who took part in the workshop on microbial bioproducts experienced an increase in knowledge about the meaning of microbial bioproducts, types and manufacturing technology. The number of participants who scored 60 and above increased by 95% in the post-test compared to the pre-test. The workshop was able to build participants' skills in making three types of microbial bioproducts, namely yogurt, biosurfactant and liquid organic fertilizer. Positive responses in the form of sentences were very useful for the workshop material, many were focused on the results of the feedback. Especially for yogurt bioproducts, almost all participants considered it very tasty, not inferior to commercial products already on the market. This shows an indication of a very high level of satisfaction. Conclusions: the understanding of community service participants on microbial bioproduct material increased through the workshop, indicated by an increasing of the participants who scored above of 60 in the post-test by 95% compared to the pre-test. Community service members' feedback through testimonials showed that 100% of the participants responded that it was very useful, indicating that the participants were very satisfied with the activity. The workshop can equip participants with skills in making yogurt bioproducts, biosurfactants and liquid organic fertilizers, which in the future are expected to be able to initiate entrepreneurship for the participants.